Evaluation of measurement accuracy of the mandible in linear and spiral tomograms - Arash Dabbaghi; Elham Rajaei; Ali Shokraneh; Hamed Tabesh; Nastaran Farhadi (Isfahan University of Medical Sciences, 2012)
Introduction: There are different radiographic imaging techniques used in dental treatments such as implants. Use of cross-sectional images, such as tomograms, enhances the visualization of the available bone. Tomographic images are prepared using 2 methods, linear and spiral. The aim of this study was to compare the accuracy of radiographic measurements in images taken by these two techniques. Materials and Methods: In this experimental study, 20 sites were selected on three dry human mandibles (10 sites anterior to and 10 sites posterior to the mental foramen) and radiographic images were taken by two techniques of linear and spiral tomography. The tomographic images were evaluated by two radiologists in relation to the variables of height and width of mandible. Then the mandibular bones were sectioned at the specified sites to determine the actual sizes of variables. The measurements from the tomograms were classified into 3 groups: error >+ 1 mm, error < -1 mm, and -1 mm < error < + 1 mm, and then were statistically analyzed by Pearson and chi-squared tests (α = 0.05).In addition, Cohen's kappa coefficient was determined to evaluate inter-observer accuracy. Results: The accuracy of radiographic measurement of linear tomography was not significantly different from that of spiral tomography, based on variable of height (p value > 0.05). Similarly, based on the variable of width, there was no significant difference between the two methods (p value > 0.05). Conclusion: Within the limitations of this study, the accuracy of the images taken by two linear and spiral tomography techniques is equal and acceptable compared to the real dimensions. Key words: Dental implant, Mandible, Tomography.